Modifikasi Modifikasi Rotor Pada Alat Pemecah kemiri Tipe Bentur - Fallo, Florianus; Pell, Yeremias M.; Pah, Jack C.A. (Universitas Nusa Cendana, 2024)
This article illustrates preparation of your paper using MS-WORD. Papers should not be numbered The rotor bar is part of the candlenut breaker tool that separates the candlenut flesh from the shell. On the rotor there is a candlenut seed intake groove which is adjusted to the size of the candlenut seed. These grooves will carry the candlenut seeds to rotate and collide the candlenuts on the wall of the stator bar which is attached to a wooden board as a support for grinding the candlenut seeds. The distance between the rotor and the wall must be adjusted in such a way as to get the desired results.